Wavelet study of dynamic variations in steel and ironmaking rest gases. Potential effect on external use - Grip, Niklas; Grip, Carl-Erik; Nilsson, Leif (Applied Energy, 2013)
The surplus energy in rest gases is an important by-product in the SSAB EMEA steel plant in Luleå. The surplus is used in a local heat and power plant. Studies have been and are being carried out to find alternative use for the high calorific gases, especially the coke oven gas. The different gas flows typically are mixtures of irregularly distributed transients and non-periodic contents of different duration. Slowly varying fluctuations can probably be parried by good production planning. For shorter wavelengths some kind of safety margin could be appropriate, perhaps in the range 0.75–1.5 kN m3/h. However, the existing buffer capacity in gasholders, etc. is too small to cover the fluctuations. Good production planning can partly compensate low buffer capacity. An example from a period without gas holder is discussed.We describe analysis of the gas flows that can be used both for better production planning and for efficient external use, e.g., for fuel production. Rather than traditional Fourier analysis, we use wavelet analysis, which is better suited for analyzing the irregular and nonperiodic characteristics of the gas flows. We demonstrate such analysis on collected gas flow data from the SSAB EMEA steel plant and give some suggestions for how to make a good choice of wavelet basis for the analyzed signals. Validerad; 2013; 20120926 (grip); Konferensartikel i tidskrift